Characterisation of heteroatomic compounds in free and bound bitumen from different source rocks by ESI FT-ICR MS. (January 2021) - Jiang, Bin; Tian, Yankuan; Zhai, Zheng; Zhan, Zhao-Wen; Liao, Yuhong; Zou, Yan-Rong; Peng, Ping'an
Highlights: Heteroatomic compounds in free and bound bitumen of source rocks were investigated. Nitrogen compounds in free and bound bitumen are mainly affected by maturity. Sulfur compound abundances in free and bound bitumen are controlled by environment. Oxygen compounds are abundant in source rocks from freshwater settings. Abstract: Catalytic hydropyrolysis (HyPy) has been widely used in the study of covalently bonded biomarkers from macromolecular organic matter. Current HyPy studies mainly focus on nonpolar aliphatic biomarkers, whereas studies of polar non-volatile heteroatomic compounds are lacking. In this study, heteroatomic compounds in free and bound bitumen released via HyPy of kerogen from three different source rocks were characterised and compared by electrospray ionisation (ESI) and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). These analyses suggest that heteroatomic compounds in bound bitumen are better proxies of the original biogenic sources and contain more aromatic structures than in heteroatomic compounds occurring in the free bitumen. From studies of three source rocks, we found that differences in the maturity, depositional environment, and diagenetic conditions seem to have significantly influenced the composition and distribution of heteroatomic compounds in free and bound bitumen. Nitrogen-containing compounds (N1 and N1 OX species) in the free bitumen were mainly affected by maturity – only being detected in the rock of highest maturity – although they occurred in similar composition in the bound bitumen of all three rocks. With increasing maturity, nitrogen compounds were partitioned from bound to free bitumen, resulting in compositional differences between these two bitumen types (especially for basic nitrogen compounds). Sulfur-containing compounds (mainly S1, OX S1, and OX S2 species) were mainly influenced by the depositional environment and were abundant in the two rocks from a reducing depositional environment. Their composition was more complex and less saturated in bound bitumen. Oxygen compounds were common to all three rocks, but of highest abundance in the one source rock deposited in a freshwater environment.